A MULTICENTRE STUDY OF ASSESSING THE EFFECTIVENESS OF SALVAGING LYMPHADENECTOMY IN PATIENTS WITH PROSTATE CANCER WITH DISEASE PROGRESSION AFTER THE RADICAL TREATMENT - B. Y. Alekseev; K. M. Nyushko; S. A. Reva; A. K. Nosov; D. G. Prokhorov; T. T. Andabekov; А. А. Krasheninnikov; E. Y. Safronova; А. S. Kalpinskiy; M. А. Gusniev; A. D. Kaprin (Исследования и практика в медицине, 2016)
Prostate cancer (PC) is one of the most urgent problems of modern oncourology because of the continuing high incidence of this pathology. The main methods of radical treatment of patients with localized and locally advanced prostate cancer are radical prostatectomy (RP) and radiotherapy – remote (RRT) or brachytherapy.  However, the frequency of biochemical markers of disease progression after curative treatment is high and reaches up to 27–53%. It is extremely important to find the tumor lesion that leads to the increase of the marker. The  palliative hormone therapy (PHT) was the only accepted method in patients with occurrence of distant metastases in recent time. However, a significant number of patients relapse marker may be associated with the so-called oligo-metastatic disease progression, in which the number of detected metastatic lesions is minimal. As the results of the research, the use of surgical or radiological treatment in selected patients of this cohort can significantly increase the length of time prior to the appointment of HT, and in some cases completely abandon its holding.Purpose. To evaluate the results of the saving pelvic lymphadenectomy in patients with prostate cancer with disease progression after radical therapies.Patients and methods. The article summarizes the results of surgical treatment of patients who have undergone life-saving lymphadenectomy about oligo-nodal metastatic progression of prostate cancer after treatment in 3 centers – P. Hertsen MORI, the branch of NMRRC; N. Petrov Research Institute of Oncology and Russian scientific center of radiology and surgical technologies. In this multicenter study they evaluated the immediate and remote results of surgical treatment of 57 patients.Results. The results performed the high efficiency of the method of the saving pelvic lymphadenectomy in patients with prostate cancer with disease progression after radical treatment. So, response to therapy and reduction in the marker level was observed in 47 (82.5%) patients. The decline in PSA level ≥50% from initial level in a month after the operation was in 38 (66,7%) patients. A complete answer in the form of lower marker ≤0.2 ng/ml was observed in 13 (22,8%) patients. For the entire median follow-up period of 12 months, patients with complete response to therapy had received any hormonal treatment.Conclusion. The saving pelvic lymphadenectomy is an effective method for the treatment of patients with the presence of lymphogenic progression of prostate cancer after a radical treatment with satisfactory oncological results. A significant contingent of patients, SLE is associated with good response to therapy and reduction in PSA levels and long disease-free period. In some patients the removal of nodal metastases allows to postpone or to abandon the HT and hope to increase overall survival of patients.